Mormonism and the emotions : an analysis of LDS scriptural texts - Properzi, Mauro (Farleigh Dickinson University Press Mormon studies series., 2015)
Mormonism and the Emotions provides the construction of an introductory Latter-day Saint (LDS) theology of emotion that is both canonically based and scientifically informed